EMPLOYEE ENGAGEMENT DAN KEPUASAN KERJA: UPAYA MENEKAN TURNOVER INTENTION KARYAWAN PERBANKAN (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
Abstract: This study aims to examine the effect of employee engagement and job satisfaction on turnover intention, where job satisfaction is also an intervening variable. The research object was the employees of Bank bjb KCK Banten with a total sample of 100 people. Data analysis using SEM-PLS method. The results of hypothesis testing show that there is a negative and significant effect of employee engagement on turnover intention, there is a positive and significant effect of employee engagement on job satisfaction, and there is a negative and significant effect of job satisfaction on turnover intention.